Integrated approach in footballers' preparedness modeling - Artem Fedetskyi (Kazimierz Wielki University, 2016)
Fedetskyi Artem. Integrated approach in footballers' preparedness modeling. Journal of Education, Health and Sport. 2016;6(12):614-624. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.220837 http://ojs.ukw.edu.pl/index.php/johs/article/view/4106         The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 754 (09.12.2016). 754 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.12.2016. Revised 20.12.2016. Accepted: 23.12.2016.       Integrated approach in footballers' preparedness modeling Artem FedetskyiLesya Ukrainka Eastern National University (Lutsk, Ukraine)   Mathematical methods have a significant place in modeling. These methods give a possibility to identify features, patterns, trends of a training process, to check the reliability of statements and assumptions. One of the conditions of successful predictions' and models' conduction is an integrated approach. It provides for a series of informative indicators that comprehensively characterize preparedness of players. To protocols, developed a comprehensive model of preparedness of the players, included anthropometric indicators, technical indicators, physical and functional training. Keywords: modeling, football players, complex approach, basic physique, technical competence.